"It is alive!" Evidence for animacy effects in semantic categorization and lexical decision. (28th May 2019) - Bonin, Patrick; Gelin, Margaux; Dioux, Vivien; Méot, Alain
Abstract: Animacy is one of the basic semantic features of word meaning and influences perceptual and episodic memory processes. However, evidence that this variable also influences lexicosemantic processing is mixed. As animacy is a semantic variable thought to have evolutionary roots, we first examined its influence in a semantic categorization task that did not make the animacy dimension salient, namely, concrete-abstract categorization. Animates were categorized faster (and more accurately) than inanimates. We then assessed the influence of animacy in two lexical decision experiments. In Experiment2, we mostly used legal nonwords, whereas in Experiment3, we varied the context of the nonwords across participants in such a way that the discriminability between words and nonwords was either high or low. Animates yielded faster decision times than inanimates when legal nonwords were used (Experiment2 ) and when the discriminability between words and nonwords was low (i.e., "difficult nonwords" in Experiment3 ), but the difference between the two types of words was not reliable when discriminability was high (e.g., illegal strings of letters, i.e., "easy nonwords" in Experiment3 ). The findings suggest that animacy is a core meaning-related dimension that influences a large number of processes involved in perception, episodic memory, and semantic memory.